2009
DOI: 10.1161/circresaha.109.196154
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 Confers Atheroprotection in apoE −/− Mice by Inhibiting LDL Oxidation via Nitric Oxide

Abstract: Atherosclerosis is promoted by a combination of hypercholesterolemia and vascular inflammation. The function of Angiopoietin (Ang)-2, a key regulator of angiogenesis, in the maintenance of large vessels is unknown. A single systemic administration of Ang-2 adenovirus (AdAng-2) to apoE ؊/؊ mice fed a Western diet significantly reduced atherosclerotic lesion size (Ϸ40%) and oxidized LDL and macrophage content of the plaques. These beneficial effects were abolished by the inhibition of nitric oxide synthase (NOS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…Our present results showed that 1 major mechanism underlying the protective effect of TrkB on CAD may be through promoting endothelial barrier's integrity. Similarly, as an angiogenic factor, angiopoietin-1 14 and angiopoietin-2 15 have been reported to protect adult vasculature integrity against atherosclerosis. TrkB has also been found in smooth muscle cell of advanced atherosclerotic lesions and to promote smooth muscle cell activity.…”
Section: Discussionmentioning
confidence: 97%
“…Our present results showed that 1 major mechanism underlying the protective effect of TrkB on CAD may be through promoting endothelial barrier's integrity. Similarly, as an angiogenic factor, angiopoietin-1 14 and angiopoietin-2 15 have been reported to protect adult vasculature integrity against atherosclerosis. TrkB has also been found in smooth muscle cell of advanced atherosclerotic lesions and to promote smooth muscle cell activity.…”
Section: Discussionmentioning
confidence: 97%
“…12 In the literature, Ang-2 signaling in vivo has been studied intensively, however, mainly by overexpression in tumor cells 22 or using adenoviruses leading to widespread cellular expression. [23][24][25][26][27] In the genetic model used within this study, Ang-2 expression is predominant in the vasculature, the physiologic site of Ang-2 expression, and as such provides an excellent tool to investigate angiopoietin signaling in vivo. .…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear FoxO1 also induces endothelial ICAM-1 and TNF-␣ expression in LDLR-deficient mice. Surprisingly, however, adenoviral overexpression of ANGPT2 in ApoE KO mice was atheroprotective, apparently through increased PKB and eNOS activity (20), while overexpression of ANGPT1 increased atherosclerosis in these mice, possibly by activation of leukocyte Tie2 (19). The interpretation of these results is complicated by potential differences in outcomes when angiopoietins are induced by adenoviral-induced overexpression versus more physiological levels.…”
Section: Endothelial Quiescence Through Tie2 Signalingmentioning
confidence: 92%